The Use Of Rückendiktat In Testing Student’s German Writing Skills In Senior High School 2 Sidoarjo - Tessalonica, Anaira Sagita; Wahyuningsih, Fahmi (LATERNE, 2025)
This study aims to examine the effectiveness of the Rückendiktat technique in improving the German writing skills of twelfth-grade students at SMA Negeri 2 Sidoarjo. Rückendiktat is a collaborative learning technique that integrates listening and writing skills through activities involving dictation and rewriting texts. This research applied a quantitative approach with a quasi-experimental design involving 34 students. The pretest results showed that 61.76% of students had writing abilities that were still categorized as low. After the intervention, the average score increased to 76.23. The paired sample t-test showed a p-value < 0.05, indicating a significant improvement in students’ writing skills. This technique has proven effective in reducing vocabulary and spelling errors and enhancing learning engagement. Rückendiktat can be implemented as an interactive and enjoyable technique in foreign language writing instruction. Keywords: Rückendiktat, writing skills, German, collaborative learning